Health literacy and mortality in individuals with NCDs: A 6-year Danish follow-up study (N = 29.473). (30th September 2020) - Friis, K; Aaby, A; Lasgaard, M; Pedersen, M H; Osborne, R H; Maindal, H T
Abstract: Background: Non-communicable diseases impact to the globally unequal distribution of health. From a public health perspective, health literacy (HL) may be a promising modifiable social determinant, suggested to be associated with adverse health outcomes. Few studies have explored how HL is related to mortality in the general population and in subgroups. This study examines HL as a predictor for mortality in the general population and among individuals with cardiovascular disease (CVD), chronic obstructive pulmonary disease (COPD), diabetes, and mental illness. Methods: Design: Data from a large Danish health survey (n = 29, 473) from 2013 were linked with national mortality registry data to permit a 6-year survival analysis using Cox regression analyses. Participants: The study included people in the general population people reporting different long-term conditions: CVD (n = 2, 389), COPD (n = 1, 214), diabetes (n = 1, 685) and mental illness (n = 1, 577). Outcome Measures: Two subscales from the Health Literacy Questionnaire (HLQ) were included: 1) Ability to understand information about health well enough to know what to do, and 2) Ability to actively engage with healthcare providers. Results: After adjusting for sociodemographic factors, multimorbidity and health behaviour, individuals reporting difficulties in understanding information about health, had higher risk of dying during follow-up (hazard rate (HR) 1.38 [95% CI 1.11-1.73]). Higher risk was also observed among people reporting CVD (HR 1.47 [95% CI 1.01-2.14]), diabetes (HR 1.91 [95% CI 1.13-3.22]) and mental illness (HR 2.18 [95% CI 1.25-3.81]), but not for individuals with COPD. Difficulties in actively engaging with healthcare providers was not associated with mortality. Conclusions: Aspects of HL predict higher risk of dying during a 6 years follow-up period. Our study serves as a reminder to public health organizations to consider the HL responsiveness of their services in relation to diverse HL challenges and needs. Key messages: Aspects of health literacy predict higher risk of dying during a 6 years follow-up period in individuals with CVD, diabetes and mental illness. Our study serves as a reminder to public health organizations to consider the health literacy responsiveness of their services in relation to diverse health literacy challenges and needs.